PENGARUH KEPEMIMPINAN, KOMUNIKASI EFEKTIF, DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL: (STUDI PADA PEGAWAI TETAP DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN KOTA YOGYAKARTA) - Erika Adinda Saputri Saputri (Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this study was to determine the effect of leadership, effective communication, and job satisfaction on organizational commitment. The method used in this study is quantitative, and the population in this study amounted to 55 respondents with data collection techniques carried out by the Simple Randlom Sampling method (probability sampling) using the slovin formula. To test the quality of the data, the researchers used validity and reliability tests. The analysis used is the classical assumption test, multiple linear regression test, and hypothesis testing. The results showed that leadership had a positive and significant effect on organizational commitment, then effective communication had a positive and significant effect on organizational commitment, and job satisfaction had a positive and significant effect on organizational commitment, leadership, effective communication, while job satisfaction had a negative and insignificant effect on organizational commitment.